Hukum Distribusi Daging Kurban Kepada Non Muslim Menurut Pandangan Mazhab Hanafi dan Mazhab Syafii - Muhammad, Ilham Akbar; SJ, Ahmad Syafi'i; Ayu, Diyan Putri (Social Science Academic, 2023)
Sacrifice is one of the worship activities in the Islamic religion which is prescribed by Allah SWT. Ulama have agreed that as a devout Muslim you should also carry out sacrifices and distribute the meat from the slaughter to the community. In practice, the implementation of sacrifice also has problems that need to be examined. One of these issues is regarding who is entitled to benefit from the slaughter, considering that in civil society life is not only inhabited by Muslims, but there are also people from non-Muslim groups. There are differences of opinion among Islamic school scholars, especially the Hanafi and Syafii schools, regarding the law on distributing sacrificial meat to non-Muslims. The Hanafi school of thought is of the opinion that it is permissible to give them meat, but there are quite a few opinions among the Shafii school of scholars who expressly forbid it. With the method of library research, which examines data based on material information obtained from the library, be it arguments, books, books, or other library works that are in the library or outside it. The approach used in this writing is a normative approach based on the theory of Thâriqâh Lafziyah and Thâriqâh Ma'nawiyyah. Based on the research conducted, there are similarities and differences that the author finds in the Hanafi and Shafii madhhabs. Both of them allow non-Muslims to get meat from sacrifices with certain conditions. While the differences in opinion that exist between the two are in the methods used. The Hanafi school emphasizes the 'urf method approach by holding the value of muamalah, while the Shafii school approaches it by expanding the meaning of the text.